Associations Between Obstructive Sleep Apnea, Metabolic Syndrome, and Sleep Duration, As Measured With an Actigraph, in an Urban Male Working Population in Japan - Chin, Kazuo (Associated Professional Sleep Societies, LLC, 2010)
BACKGROUND: Severe obstructive sleep apnea (OSA), metabolic syndrome (Mets) and short sleep duration are all risk factors for cardiovascular events. There has been no report which has investigated this relationship in an age- and BMI-matched population-based study. The prevalence of OSA in Mets subjects has not been established, although the converse (i.e., the prevalence of Mets in OSA subjects) has been investigated several times. METHODS: This home cardiorespiratory (type 3) sleep study, using an actigraph, was conducted in 275 males working for an urban company. Retrospective measurements of fasting blood parameters were obtained from the company's periodical inspection data. The mean duration between the sleep study and the measurement of blood parameters was 213 days. RESULTS: Although there was a significant relationship between OSA severity and the prevalence of Mets (P < 0.001), the association between severity and Mets was not significant after adjustments were made for age and BMI. Severe OSA was 7.8 times as likely to be present in subjects with Mets (16.2% of all 68 Mets subjects) as those without (2.4% of 207 non-Mets) (P < 0.001). Subject with severe OSA had a significantly short sleep duration (P < 0.05). Sleep duration in Mets subjects was also significantly shorter than in those without (P < 0.05). CONCLUSIONS: Although increased BMI and age both had a significant effect on the prevalence of OSA in patients with Mets, one of 6 subjects with Mets, but only one of 40 without Mets had severe OSA in an urban male population in Japan. Physicians should take into account this high prevalence of severe OSA in patients with Mets. Sleep duration should be taken into consideration as an important factor in studies investigating the prevalence of severe OSA and Mets. CITATION: Chin K; Oga T; Takahashi K; Takegami M; Nakayama-Ashida Y; Wakamura T; Sumi K; Nakamura T; Horita S; Oka Y; Minami I; Fukuhara S; Kadotani H. Associations between obstructive sleep apnea, metabolic syndrome, and sleep duration, as measured with an actigraph, in an urban male working population in Japan. SLEEP 2010;33(1):89-95.